The prescribing trend of oral antidiabetic agents for type 2 diabetes in Taiwan: An 8-year population-based study. Issue 43 (October 2017) - Chu, Wei-Min; Ho, Hsin-En; Huang, Kuang-Hua; Tsan, Yu-Tse; Liou, Yi-Sheng; Wang, Yueh-Hsin; Lee, Meng-Chih; Li, Yu-Ching
Abstract : Abstract: The purpose of this study was to evaluate the prescription trend and pattern of oral antidiabetic (OAD) medications, which are extensively used worldwide for treating type 2 diabetes, in 2 age groups. In this population-based study, data obtained from the National Health Insurance Research Database, Taiwan, were analyzed to investigate the prescription trend of all types of OAD medications during 2005 to 2012. We used descriptive statistics to demonstrate the trend of prescription patterns stratified by age (aged 65 years and above or younger than 65). Sulfonylurea (SU) was once the most commonly used drug, but the proportion of its prescription had declined gradually (76.83% in 2005 to 63.70% in 2012). Consequently, biguanide (BG) became the most commonly used drug since 2010 (64.31% in 2005 to 74.41% in 2012). In addition, the prescriptions of thiazolidinedione decreased significantly (9.20% in 2005 to 2.86% in 2012), whereas the usage of DPP-4 inhibitor increased with time (3.73% in 2009 to 19.64% in 2012). The treatment choice of SU and α-glucosidase inhibitor (AGI) was higher in elderly patients compared with the younger population (SU: 62.70% in 2012, AGI: 12.78% in 2012). Two-drug combination therapies were the prevalent treatment choices for patients with type 2 diabetes (44.77% in 2012), particularly in the elderly group; however, ≥3 drug combination therapies increased gradually during the study period, particularly in the younger group. This descriptive study presents the change in the prescription of OAD medication for different age groups during 2005 to 2012.